The Elasticity of Substitution between Domestic and Foreign Goods: A Quantitative Survey - Jozef Bajzik; Tomas Havranek; Zuzana Irsova; Jiri Schwarz (ZBW – Leibniz Information Centre for Economics, 2019)
A key parameter in international economics is the elasticity of substitution between domestic and foreign goods, also called the Armington elasticity. Yet estimates vary widely. We collect 3,524 reported estimates of the elasticity, construct 34 variables that reflect the context in which researchers obtain their estimates, and examine what drives the heterogeneity in the results. To account for inherent model uncertainty, we employ Bayesian and frequentist model averaging. We present the first application of newly developed non-linear techniques to correct for publication bias. Our main results are threefold. First, there is publication bias against small and statistically insignificant elasticities. Second, differences in results are best explained by differences in data: aggregation, frequency, size, and dimension. Third, the mean elasticity implied by the literature after correcting for both publication bias and potential misspecifications is 3.
Keywords: C83; D12; F14; 330; Armington; trade elasticity; meta-analysis; publication bias; Bayesian model averaging